2022
DOI: 10.3389/fevo.2022.1058746
|View full text |Cite
|
Sign up to set email alerts
|

Neontological and paleontological congruence in the evolution of Podocarpaceae (coniferales) reproductive morphology

Abstract: IntroductionPodocarpaceae are a diverse, primarily tropical conifer family that commonly produce large leaves and highly reduced, fleshy seed cones bearing large seeds. These features may result from relatively recent adaptation to closed-canopy angiosperm forests and bird-mediated seed dispersal, although determining precisely when shifts in leaf and seed cone morphology occurred is difficult due to a sparse fossil record and relatively few surviving deep lineages.MethodsWe compare the fossil record of Podoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…The number of prosuspensor cells varies widely in the Podocarpaceae (Table 2), and it ranges from seven to twenty-three in the Podocarpoid clade and from five to fourteen in the Dacrydioid clade. The number is lower in other reported Podocarps (3)(4)(5)(6), and there is variable reporting of the number of binucleate cells and elongating cells present. The reproductive cycle varies from one to two years.…”
Section: Ovule and Embryo Traitsmentioning
confidence: 58%
See 2 more Smart Citations
“…The number of prosuspensor cells varies widely in the Podocarpaceae (Table 2), and it ranges from seven to twenty-three in the Podocarpoid clade and from five to fourteen in the Dacrydioid clade. The number is lower in other reported Podocarps (3)(4)(5)(6), and there is variable reporting of the number of binucleate cells and elongating cells present. The reproductive cycle varies from one to two years.…”
Section: Ovule and Embryo Traitsmentioning
confidence: 58%
“…The Podocarpoid clade species have relatively large seed cones (Supplementary Figure S4). Furthermore, Leslie et al [50] reported that seed sizes are generally larger in animal dispersed species [5]. The number of seeds per cone varies in the Podocarpoid clade from one to two, which have, for example, been reported in Podocarpus [51].…”
Section: Broader Perspective With Other Podocarpsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Jurassic to Early Cretaceous increase in conformable edges among many conifer clades coincides with a shift towards thicker and more heavily armored seed cones [22,65], a pattern that mirrors microevolutionary changes in extant conifer populations experiencing high predation pressure from birds and mammals [66,67]. At the same time, fleshy seedcovering organs and compact fruit-like cones that likely functioned in vertebrate seed dispersal become notable features of other conifer clades [68,69], members of the Gnetales [70] and extinct gymnosperms like Caytonia, whose cupules have been recorded in coprolites [71]. Stronger ecological interactions with vertebrates, particularly as small-bodied birds and mammals radiated from the Jurassic onwards [69,72,73], may have favoured the evolution of more compact reproductive structures better adapted to either protect seeds or function as small edible diaspores [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, fleshy seedcovering organs and compact fruit-like cones that likely functioned in vertebrate seed dispersal become notable features of other conifer clades [68,69], members of the Gnetales [70] and extinct gymnosperms like Caytonia, whose cupules have been recorded in coprolites [71]. Stronger ecological interactions with vertebrates, particularly as small-bodied birds and mammals radiated from the Jurassic onwards [69,72,73], may have favoured the evolution of more compact reproductive structures better adapted to either protect seeds or function as small edible diaspores [74,75]. These morphologies appear to be largely derived from existing morphological elements, however, rather than new suites of organs, resulting in a diverse range of morphological strategies for covering seeds (e.g.…”
Section: Discussionmentioning
confidence: 99%